A review: nutrition quality and processing of Malaysian strawberries - Shamsuddin, Rosnah; Hamzah, Hanny Zurina; K., Shuso; E., Yasunaga; Mahat, Fauziah (Rynnye Lyan Resources, 2020)
Malaysian strawberries planted in the Cameron Highlands region are mostly done by small-scale farmers and often face post-harvest losses due to the highly perishable nature of strawberries and lack of information on available processing technologies. This review intended to give an overview of the nutritional quality of strawberries, post-harvest factors that contribute to quality decrement and processing practices done to reduce losses as well as increase the shelf-life of strawberries. Literature comparison between Malaysia and other countries was done on available prior studies and written reports. The review revealed that strawberries are rich in anthocyanin (which contributes to its red colour and flavour) and vitamin C, high in moisture content (up to 92% at ripening stage), have an acidic pH (ranging from 3.39 to 3.8 upon ripening) and sweet in taste (glucose, fructose and sucrose are the major soluble sugars available in strawberries). Several factors contributed to strawberry fruits losses and deterioration including the effect of improper handling, storage condition and pathogen bacteria attack. Drying and pasteurisation processes are the most common practices done in strawberry processing due to the effectiveness of the treatments in extending their shelf-life.